Numerical Analysis of a Mechanical Wave Damping in the Rubber-Concrete Composite using the Adina Software - Major, Izabela; Major, Maciej; Kucharova, Daniela (Communications - Scientific letters of the University of Zilina, 2016)
This paper presents numerical analysis concerning a rubber-concrete composite which can be considered as a structural element designed to form walls. Structural elements that carry the compressive load have a rubber with a specific shape embedded during the technological process. Therefore, the prefabricated block offers an additional damping property of a mechanical wave resulting from the dynamic load. The numerical analysis using the ADINA software revealed significant mechanical wave damping in the composite analysed in the study for different types of dynamic load.